2014
DOI: 10.7314/apjcp.2014.15.18.7843
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Postsurgical Management in Young and Elderly Breast Cancer Patients Results in Equal Survival Rates

Abstract: Background: Although breast cancer (BC) is one of the most common malignant diseases in women, the majority of the studies describing the characteristics of BC in elderly patients have been limited to survival assessments or tumor features, without using younger BC patients as a reference group. The aim of our study was to describe and compare tumor characteristics and management patterns in elderly versus younger breast cancer patients in Turkey. Materials and Methods: We retrospectively analyzed 152 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
(74 reference statements)
0
5
0
2
Order By: Relevance
“…Breast cancer is one of the most common types of malignant tumor and is a serious threat to the health of the patient (12). A previous study found that there was no expression of P2X7R in normal breast tissues; however, P2X7R was overexpressed in breast cancer tissue (13).…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is one of the most common types of malignant tumor and is a serious threat to the health of the patient (12). A previous study found that there was no expression of P2X7R in normal breast tissues; however, P2X7R was overexpressed in breast cancer tissue (13).…”
Section: Discussionmentioning
confidence: 99%
“…Grade, Ki-67, and molecular subtypes are important prognostic factors for breast cancer (21). Young patients with breast cancer have been reported to have a higher proliferation rate,more grade 3 tumors, and worse molecular subtypes (3,22,23). Breast cancer has different biological properties that vary from person to person.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that younger patients are diagnosed at more advanced stages due to lack of screening mammography, dense breast parenchymal structure, and low awareness of patients (19,23,25). Reviews indicating that younger patients present with advanced staged breast cancer have also been published (26).…”
Section: Discussionmentioning
confidence: 99%
“…Histolojik grade, Ki-67 ve moleküler alt tipler meme kanserinde önemli prognostik faktörlerdendir (20) . Genç yaştaki meme kanserli hastaların daha yük-sek proliferasyon oranına ve daha kötü moleküler alt tiplerine sahip oldukları bildirilmiştir (7,21) . Göksu ve ark.…”
Section: Discussionunclassified
“…Yaş gruplarına bakılmaksızın semptomatik olarak ilk baş-vuru sonucunda saptanan meme kanseri tanısında daha ileri evreler görülebilmektedir. Genç yaştaki grupta meme kanserinin tarama mamografisinin yapı-lamaması, hızlı metabolizma nedeniyle tümörün hızlı büyüdüğü görüşü, memenin yoğun parankimal yapı-sı, hasta farkındalığının düşük olmasından dolayı daha ileri evrelerde tanı konulduğu bildirilmiştir (7,17,21) . Çalışmamıza göre tanı sırasında meme kanserinin evresi hastanın yaşına göre değişmemektedir.…”
Section: Discussionunclassified